Nature – a Medium of Value in a Constructivist Pedagogy - Buchcic, Elżbieta (Annales Universitatis Paedagogicae Cracoviensis. Studia ad Didacticam Scientiarum Socialium Pertinentia, 2020)
In Polish pedagogy, at the time of change, there is a reflection on the way of educating young people and on the need of creating a new educational system. Groundbreaking systems and educational methods are being searched for. The new ones are being created but also the old proven ways that have permanently made the educational process, both in formal and informal education, are used again. In the article, it is brought to attention that nature is an inherent element of every human’s life and should be a value to them. It should also be kept in mind that knowledge is not only facts, laws and theories drawn from observation of phenomenons and occurrences but is also the ability to use it rationally and to interpret information in everyday life. Using premises of constructivist pedagogy in formal and informal education, one can or even should form axiological paradigms of nature.